KESIAPAN GURU DALAM MENERAPKAN PENDEKATAN PEMBELAJARAN MENDALAM DI SDN 167 PEKANBARU - Dian Surya Lestari; Zaka Hadikusuma Ramadan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teachers' readiness in implementing the deep learning approach at SDN 167 Pekanbaru, examined from the aspects of planning, facilities and infrastructure, implementation, and evaluation of learning. This study employed a qualitative method with a phenomenological approach. The research informants consisted of three homeroom teachers as key informants, the school principal as an expert informant, and students as supporting informants. Data were collected through interviews, observations, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The results show that teachers at SDN 167 Pekanbaru demonstrated good readiness in implementing the deep learning approach. Teachers were able to design Deep Learning Lesson Plans, select appropriate learning models and media, and were supported by adequate facilities and infrastructure. At the implementation stage, teachers applied the principles of mindful, meaningful, and joyful learning, complemented by continuous evaluation through diagnostic, formative, and summative assessment, as well as reflection. Nevertheless, several constraints were found, such as limited time, the diversity of students' characteristics, and the limited number of technological facilities.